Kaghaz kaisay banta hay? - Asimof Isak (Ferozesons; PAKISTAN, 2002)
Chaand Apni Shakal Kyun Badalta Hai? explores the scientific and poetic explanation of the moon's phases, blending curiosity with wonder.